Reducing stress and alcohol-related behaviors by targeting D1-CRHR1 receptor interactions in the amygdala - Broccoli, Laura; Bernardi, Rick E.; Giannone, Francesco; Hoppe, Anika; Jungling, Kay; Borroto-Escuela, Dasiel O.; Rimondini-Giorgini, Roberto; Pérez de la Mora, Miguel; von Bohlen und Halbach, Oliver; Fuxe, Kjell; Pape, Hans-Christian; Deussing, Jan M.; et al. (Frontiers in pharmacology, 2025)
BackgroundBasic neuroscience has identified dopamine and corticotropin-releasing hormone (CRH) systems and amygdala circuits as key contributors to drug and alcohol reward, craving, and relapse. However, directly targeting these systems has had no impact on the treatment of addictive disorders. CRH receptor 1 (CRHR1) and dopamine receptor D1 are both modulators of amygdala function. The intercalating cell masses (ITC) regulate intra-amygdala signal flow and are highly enriched in CRHR1 and D1. To date, interactions between these systems have not been extensively examined. We tested these interactions using a combination of in vivo pharmacology, genetic targeting and behavioral studies in rodents.MethodsThe impact of CRHR1 activation on D1 was demonstrated using i. c.v. injection of either CRH (2 μg/μL) or stressin I (4 μg/2 μL) in naïve rats followed by D1 receptor autoradiography. We then injected stressin I (0.01 μg/0.5 μL) and stressin I in combination with the D1 antagonist SCH23390 (120 ng/0.5 μL) site-specifically into the ITC and tested animals in the Elevated-Plus-Maze (EPM), followed by saturated D1 receptor autoradiography. Alcohol dependence was also induced in rats and D1Cre-Crhr1−/− knockout mice via cyclic intermittent alcohol vapor exposure. Following abstinence, rats were used for D1 expression analysis (in situ hybridization, D1 autoradiography) and assessment of morphological changes using Golgi-impregnation. In addition, abstinent D1Cre-Crhr1−/− mice were analyzed for alcohol drinking and stress-related alcohol drinking (Two-Bottle-Free-Choice, Forced Swim Stress-induced drinking). Double-immunofluorescence immunostainings were performed for D1 and CRHR1 in the amygdala of Crhr1-GFP reporter mice.ResultsPharmacological activation of CRHR1 by i. c.v. injection of CRH or stressin I increased D1 binding sites exclusively in the amygdala, but not in extra-amygdala brain regions. Site-specific CRHR1 activation in the amygdala/ITC was associated with increased anxiety-like behavior that was prevented by co-treatment with SCH23390. In dependent D1Cre-Crhr1−/− mice, the D1-CRHR1 interaction appears to be critically involved in maladaptive stress coping and increased relapse propensity. Our immunohistochemical findings also suggest the D1-CRHR1 interaction is dependent on co-localized receptors.ConclusionOur findings suggest D1-CRHR1 interactions within the ITC of the amygdala in response to stress, alcohol behavior, and the development of dependence, thereby providing a novel mechanism that may be targetable by therapeutic polypharmacological interference.
Veröffentlicht: 16. Oktober 2025
Gesehen am 09.12.2025